Karakter Wirausaha pada Industri Mikro Pangan Olahan di D.I.Y dan Faktor-Faktor yang Mempengaruhi - Triwara Buddhi Satyarini (AGRARIS: Journal of Agribusiness and Rural Development Research, 2016)
Study about entrepreneurial character of micro business processed foods maker in the province of Yogyakarta covering 5 districts was conducted. The sample used on this study was they who are have many firm in each district. The study aims to determine the character of the entrepreneurs and analyzed its relationship with business performance, especially in terms of the efficiency of their business. Descriptive analysis was used to find out entrepreneurial character based on data assessed with Liekert’s scales and use path analysis to determine the relationship between entrepreneurial character with efficiency in its business performance. The results of the analysis showed that the entrepreneurial character of the businessmen in general was less strong. External environmental factors were conducive, although the social environment factors were less supportive. Family support was the only one that high. Leadership has a strong influence on future orientation, character of ownership of the business, responsivity and creativity to facing change. Character of leadership was in a strong level so that, if improved, it will enhance the character of entrepreneurial capacity. Characters of future orientation also exist at the strong level.